Mitigating the Adverse Effects of Salt Stress on Pepper Plants Through Arbuscular Mycorrhizal Fungi (AMF) and Beneficial Bacterial (PGPR) Inoculation - Sultan Dere (Horticulturae)
This study investigates arbuscular mycorrhizal fungi (AMF), plant growth-promoting rhizobacteria (PGPR), and their combined application under salt stress (200 mM NaCl), emphasizing their synergistic potential to enhance plant resilience. Conducted in a controlled climate chamber, key parameters such as plant height, biomass, SPAD values, ion leakage, relative water content (RWC), osmotic potential, and mineral uptake were assessed. Salt stress significantly reduced plant growth, chlorophyll content, and nutrient absorption. However, AMF and PGPR improved plant performance, with co-inoculation showing the highest efficacy in increasing RWC, nutrient uptake, and maintaining membrane stability. AMF and PGPR treatments enhanced potassium retention and reduced sodium and chloride accumulation, mitigating ionic imbalances. The improved chlorophyll content and water relations under co-inoculation demonstrate the potential of these biostimulants to boost photosynthesis and plant resilience. These findings highlight AMF and PGPR as eco-friendly solutions for sustainable agriculture, promoting crop productivity and stress tolerance under saline conditions.